Pemberdayaan Lembaga Pers Siswa dalam Meningkatkan Literasi Jurnalistik di MTs. Sunan Drajat Banjarwati Paciran Lamongan - R. Zainul Mushthofa; Siti Aminah; Ike Nurul Fitrotus Shoimah; Reni Reni (Santri: Journal of Student Engagement, 2023)
Literacy-based education should be familiarized in the world of education, let alone journalism in schools. The millennial generation have to the ability to write, both in the field of journalism and non-journalism. On that basis, our real-life college service team empowers student press institutions. Through journalistic literacy, it will teach students to have creativity in writing and be aware of the importance of journalism and the press. The method we use in this service is ABCD-Asset or potential based community development. The results we got through our activities were in the form of socialization and introduction of the service team with student press institutions, providing journalistic and press materials, mentoring young journalists, the practice of making wall magazines, training in layouting and editing techniques for wall bulletins and success in making educational wall magazines by The Students of Press Institutions. From these activities, the results obtained are that The Students of Press Institution are familiar with journalism and the press, know the techniques of interviewing and compiling news, understand the rubrics in wall magazines and can make opinions, articles, short stories and so on, able to make good wall magazines and know the layouting and editing techniques of wall bulletin scripts.